Modulation of Warfarin Sodium into Warfarin Potassium for Patients with Hypertension (Global Journal of Science Frontier Research, 2022)
Abstract not found
Keywords: warfain; hypertension; international normalized ratio; therapeutic window; clinical trials; pharmaco-genomics; CYP2C9*3